1980
DOI: 10.1111/j.1365-2133.1980.tb01687.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed skin test reactivity to Propionibacterium acnes correlates with severity of inflammation in acne vulgaris

Abstract: Propionibacterium acnes is the bacterial species most consistently isolated from acne lesions. Intradermal injection of a heat-killed suspension of P. acnes induced a delayed erythematous and often popular inflammatory reaction which was maximal after 24-48 h. This response was dose related and was probably mediated at least partly by immune mechanisms. In eighty-one subjects with acne of varying severity of the acne. These findings indicate that the host response to P. acnes is an important variable in determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
2

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 17 publications
2
21
0
2
Order By: Relevance
“…Puhvel et al [22]showed that lymphocyte stimulation by P. acnes is significantly increased in patients with nodulocystic acne. Kersey et al [23]demonstrated that delayed skin test reactivity to P. acnes correlates with the severity of the disease. Recent studies performed by Jappe et al [24]revealed that P. acnes could activate both peripheral blood mononuclear cells of adults and cord blood mononuclear cells and that the reactions produced are both antigenic and T cell mitogenic.…”
Section: Abnormalities Of the Microbial Floramentioning
confidence: 99%
“…Puhvel et al [22]showed that lymphocyte stimulation by P. acnes is significantly increased in patients with nodulocystic acne. Kersey et al [23]demonstrated that delayed skin test reactivity to P. acnes correlates with the severity of the disease. Recent studies performed by Jappe et al [24]revealed that P. acnes could activate both peripheral blood mononuclear cells of adults and cord blood mononuclear cells and that the reactions produced are both antigenic and T cell mitogenic.…”
Section: Abnormalities Of the Microbial Floramentioning
confidence: 99%
“…A delayed type hypersensitivity was also suggested by Kersey et al [296] who performed skin testing by using heat-killed P. acnes in acne patients. The intensity of the response was correlated with the severity of acne [296]. For Norris and Cunliffe [297] the infiltrates were mainly lymphoid in the 6- and 24-hour biopsies of inflammatory lesions.…”
Section: Inflammation: Evolving Actor In Acne Pathogenesismentioning
confidence: 67%
“…Intradermal injection of P. acnes provokes an inflammatory reaction suggestive of cell-mediated delayed allergy [250]. A delayed type hypersensitivity was also suggested by Kersey et al [296] who performed skin testing by using heat-killed P. acnes in acne patients. The intensity of the response was correlated with the severity of acne [296].…”
Section: Inflammation: Evolving Actor In Acne Pathogenesismentioning
confidence: 97%
“…The delayed-type hypersensitivity reaction in acne appears to be mounted against one or more propionibacterial antigenic components (13,16,38). While it is not a life-threatening condition, acne can have serious psychological and socioeconomic consequences that severely affect a patient's quality of life (7,14,15,18).…”
mentioning
confidence: 99%